Partisipasi Masyarakat Wanita dalam Aspek Ekonomi di Desa Botto Mallangga Kecamatan Maiwa Kabupaten Enrekang - Suci Nur Ramadani; Hariyanti Hamid; Andi Astinah Adnan; Muhammad Nur (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the participation of women in the economic aspect in Botto Mallangga Village, Maiwa District, Enrekang Regency. The population in this study is 778 women. This study uses two types of variables, namely variable X (women's participation) and variable Y (economic aspect). The sampling technique used a random sample of 89 people. This type of research is quantitative associative. The data collection techniques used in this study are observation, questionnaire, literature study. The data analysis technique used was a validity and reliability test using the help of the IBM SPSSS statistical 26.0 application. The results of this study show that the participation of the female community is "Influential/Significant" in the economic aspect in Botto Mallangga Village, Maiwa District, Enrekang Regency, based on the results of the recapitulation of the community participation variable with a percentage result of 73% in the good category and the recapitulation of the economic aspect variable with a percentage result of 72.8% in the good category. The factors that affect the participation of women in the economic aspect with a percentage result of 70.2% are in the good category.